Review on Application of Rotating Biological Contactor in Removal of Various Pollutants From Effluent - Mizyed, Amjad (Technium BioChemMed, 2021)
Biological wastewater treatment is an essential area of research in the environmental sector due to its distinct benefits and applicability. Two-thirds of the world is at risk of water shortages, so safe disposal and reuse of wastewater is the most challenging task. Rotating biological contactors (RBC) comprise a unique and ascendant alternative for wastewater treatment and removal of various pollutants. This review paper discusses the application of several aspects of the (RBC) system with detail to its features, operating parameters, as well as factor affected efficiency with related to media, system configuration, flow rate design, biofilm mechanism, and influent characterization, which are presented in this paper. The review of research carried out the outline of common applications such as nitrification, denitrification, and phosphorus removal and focus on recent utilization of (RBC) in high load industrial wastewater treatment, pharmaceuticals and complex compound removal, and chemical agriculture waste bioremediation. In addition to that, mentioning the integration with other biological technology to increase the efficiency and attaining high effluent quality. Novel (RBC) units include approaches for energy generation as the direct current generation. (RBC) has been used very successfully in lab-scale and some consideration in scale-up. Full nitrification is attainable under suitable process conditions while phosphorus removal and denitrification as yet necessitate extra exploration. This review is an ideal contender for the hybrid system which provide a relation between specialist and debate latest developments in RBC research to achieve high-quality stream, reducing energy consumption and make the most of efficiency.